A Phytophthora sojae Glycoside Hydrolase 12 Protein Is a Major Virulence Factor during Soybean Infection and Is Recognized as a PAMP. Issue 7 (10th July 2015) - Ma, Zhenchuan; Song, Tianqiao; Zhu, Lin; Ye, Wenwu; Wang, Yang; Shao, Yuanyuan; Dong, Suomeng; Zhang, Zhengguang; Dou, Daolong; Zheng, Xiaobo; Tyler, Brett M.; Wang, Yuanchao
Abstract : Phytophthora sojae produces the xyloglucan-degrading enzyme XEG1 as a virulence factor; this apoplastic effector is also recognized via the plant's PAMP recognition machinery. Abstract: We identified a glycoside hydrolase family 12 (GH12) protein, XEG1, produced by the soybean pathogen Phytophthora sojae that exhibits xyloglucanase and β-glucanase activity. It acts as an important virulence factor during P. sojae infection but also acts as a pathogen-associated molecular pattern (PAMP ) in soybean ( Glycine max ) and solanaceous species, where it can trigger defense responses including cell death. GH12 proteins occur widely across microbial taxa, and many of these GH12 proteins induce cell death in Nicotiana benthamiana . The PAMP activity of XEG1 is independent of its xyloglucanase activity. XEG1 can induce plant defense responses in a BAK1-dependent manner. The perception of XEG1 occurs independently of the perception of ethylene-inducing xylanase. XEG1 is strongly induced in P. sojae within 30 min of infection of soybean and then slowly declines. Both silencing and overexpression of XEG1 in P. sojae severely reduced virulence. Many P. sojae RXLR effectors could suppress defense responses induced by XEG1, including several that are expressed within 30 min of infection. Therefore, our data suggest that PsXEG1 contributes to P. sojae virulence, but soybean recognizes PsXEG1 to induce immune responses, which in turn can be suppressed by RXLR effectors. XEG1 thus represents an apoplastic effector that is recognized via the plant's PAMP recognition machinery.